APPLICATION OF PHYSICAL AND CHEMICAL METHODS IN TREATMENT OF PURULENT DISEASES OF SOFT TISSUE (Archive of Conferences, 2020)
The increase in the number of postoperative infectious complications, as well as purulent diseases of soft tissues, the low efficiency of most conventional methods of therapy, the duration of treatment in modern conditions for the treatment of purulent wounds and the stimulation of their healing are one of the problems of surgery. Therefore, the search for new ways of treating this pathology remains a necessary task for clinicians.